Effects of Hydraulic Dredging for Mercenaria mercenaria, Northern Quahog, on Sediment Biogeochemistry. Issue 3 (June 2014) - Meseck, Shannon L.; Mercaldo‐Allen, Renée; Rose, Julie M.; Clark, Paul; Kuropat, Catherine; Pereira, Jose J.; Goldberg, Ronald
Abstract A before‐after‐control‐impact (BACI) experiment was conducted to examine the effects of hydraulic clam dredging on sediment biogeochemistry of a leased shellfish bed of Mercenaria mercenaria, northern quahog, over the course of an entire growing season. Six study plots (0.67 ha each), three dredged and three not dredged, off of Milford, Connecticut, in Long Island Sound, were sampled from May to October 2009 for porewater fluxes of total ammonia, oxygen, and hydrogen. Particulate samples were also analyzed for grain size, total nitrogen, total carbon, total sulfur, and organic carbon. Statistical analysis indicated no significant difference between dredged and not dredged sites. Grain size and oxygen flux explained 22% of the variation in the total benthic species assemblages; grain size and either total carbon or organic nitrogen explained 18% of the variation in molluscan abundance. Our study demonstrates that one‐time hydraulic shellfish harvesting had minor effects on the sediment chemistry of a leased clam bed.